Appeals against decisions ordering preventive measures - Mihai, Larisa-Elena (Technium Social Sciences Journal, 2023)
The Criminal Code highlights facts that constitute crimes and sanctions that can be applied to those who violate them in order to protect the interests of society, legal entities and citizens. The authorities are charged with enforcing the sanctions of the Criminal Code and other consequences, and the accountability of offenders must be done according to specific standards, corresponding to the needs of two major interests: the interests of society and individual interests. Carrying out normal work involving the rapid detection of crimes and the identification of offenders, as well as the implementation of legal consequences that serve as a means of combating and preventing crime, is in the interest of society. Individual interests demand that this activity be strictly regulated by law, with abuses and injustices outlawed, as well as provide citizens with effective ways to defend themselves against a false accusation or more serious than the real one. Official participants in criminal proceedings must do their job objectively and impartially to administer good repressive justice. The law has developed remedies to protect against unfounded or illegal judgments, as well as mistakes committed by courts or other entities with jurisdiction. These remedies may include checking illegal or unfounded decisions and correcting errors